Management of Type 2 diabetes: Treating targets and strategies - S. Joshi; P. Joshi (South African Family Practice)
Guidelines for care and treatment goals as recommended by the International Diabetes Federation and the American Diabetes Association (ADA) are presented, together with the recent consensus document from the ADA and the European Association for the Study of Diabetes. Targets for control are presented as therapeutic targets to be obtained. The current approaches to therapy include lifestyle modifications, diet, oral agents and insulin therapy. An algorithm is presented as a practical approach to manage Type 2 diabetes. Some newer agents that will become available in the near future in our country are mentioned. This article outlines the pathophysiology of Type 2 diabetes, emphasising the roles of insulin resistance and insulin deficiency in its aetiopathogenesis. The liver, peripheral tissues and the pancreas are the three important role players in this condition.